Seaborne Patrollers Performance Evaluation: A Framework for A Proposed Development Plan - Tutaan, Mary Jaemee Lauren; Bakingkito, PLT Rochelle G; Atanacio, Precious F.; Dauis, Dennis Victor S.; Malang, Bernandino P.; Vigonte, Florinda G. (Future Science / FSH-PH Publications, 2023)
The study focused on the analysis of the work performance of the seaborne patrollers through their individual performance evaluation reports. The study aimed to evaluate the overall performance standing of the police officers in terms of their output, core competencies, and personal qualities which would be the basis for a proposed developmental framework that would maximize the capacity and capability of the personnel of the PNP Maritime Group. The respondents of the study were the police officers of the PNP Maritime Group in the municipality of Pangasinan composed of sixty-six (66) police non-commissioned officers and nine (9) police commissioned officers. The researcher used the descriptive method of research to obtain factual and quality data and aided the researchers in describing and explaining the current situation. The researchers used Individual Performance Evaluation Report (IPER) to measure the respondents' work and personal qualities. The data was manually encoded by the researchers using Microsoft Excel accurately to attain descriptive validity. Upon analyzing the gathered data, it was found that the high level of scores extracted from the respondents' Individual Performance Evaluation Report (IPER) is highly capable of their mandate as police officers. There are also enhancements presented in the study that needs to be integrated with the need to be integrated with the existing program to create opportunities to develop personal and professional qualities. In turn, this better and more responsive organization. Among the recommendations observed in the study are the following: maintaining the practice of the Individual Performance Evaluation Report (IPER); adopting the developmental plan; crafting the scorecard as an instrument that would translate the aspects of the Individual Performance Evaluation Report (IPER) into a more understandable and detailed plan for the development of the individual; implementing refresher course and orientation for new police officers on the importance of Individual Performance Evaluation Report (IPER) not only as compliance at work but more so as an instrument to grow and develop personally and professionally; the implementation of the Individual Performance Evaluation Report (IPER) program must be further studied in terms of process and evaluation; there must be a holistic evaluation and monitoring process for every project or program in connection with the Individual Performance Evaluation Report (IPER), and lastly, there must be a program to monitor the effectiveness of the Individual Performance Evaluation Report (IPER) as time continues, checking on its relevance, and looking for weak points to improve and strong points to standardize.